Artificial and Spiritual Intelligence Synergy in Madrasah Digital Transformation - Iwan Hermawan; Oyoh Bariah; Nur Aini Farida (Cendekia: Kependidikan dan Kemasyarakatan, 2026)
This study examines the synergy between artificial intelligence (AI) and spiritual intelligence (SI) in the digital transformation of State Islamic Senior High Schools (MAN) in Karawang Regency in the Society 5.0 era. Specifically, it aims to: (1) identify AI utilization in pedagogical and administrative practices; (2) analyze its impacts, supporting factors, and barriers; and (3) formulate an empirical model of AI–SI synergy for value-based madrasah transformation. This study employed an explanatory sequential mixed-methods design involving 235 respondents: principals, teachers, administrative staff, students, and community/religious leaders. Data were collected through online questionnaires, semi-structured interviews, documentation analysis, and direct observation. Quantitative data were analyzed descriptively, while qualitative data were interpreted through condensation, display, and verification. The findings reveal that AI is used for learning material development, interactive assessment, attendance automation, grade processing, and digital archiving. AI improves learning effectiveness and administrative efficiency, supported by institutional policy and innovation motivation, yet constrained by unstable internet access and limited technical training. More importantly, AI–SI synergy emerges when AI serves as a cognitive-administrative assistant, while teachers remain muaddib through five Islamic value pillars: amanah, ikhlas, responsibility, adab, and tawakal. The study concludes that Civilized AI provides an ethical framework for madrasah digital transformation.